Liberating Voices for Equity – Exploring Cultural Minority Students’ Experiences in an Integrated Classroom - Kudakwashe, Kapofu Lifeas; Angela, James; Michelle, Stears (Advances in Social Sciences Research Journal, 2022)
This study foregrounds cultural minority learners’ voices in the exploration of accomplishment of socio-cultural redress in basic education. The resonating global call within the socio-cultural movement is for the inclusion of marginalised voices and epistemes in curricula reformation and transformation overtures. Heeding the latter, this study within the context of decolonisation, ethical professional practice and equity sought to establish experiences of cultural minority learners’ experiences in an integrated South African school. Conceptually framed within Culturally Responsive Pedagogy (CRP) as strategy for pedagogical equity and pursued through a naturalistic methodology scaffolded by observation and interviewing the study elevates cultural minority learners’ voices about the pedagogic setting. The study found that minority students regarded the architecture of teaching and learning context as structured by their teachers as: marginalising; alienating, disenchanting; emasculating; constraining, not attendant to their intrinsic motivation needs nor their socio-political identities. Findings revealed that though the legislated architecture for equity through cultural inclusivity exists vestigial classroom practices not attuned to these aspirations for equity still persist. Such findings highlighted the need for an escalation of deliberate interventions to overturn these historically nuanced inhibitions to create equitable pedagogic settings.